An increasing trend and impact of non communicable diseases in Vanuatu - Wesley Donald (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Non Communicable Diseases (NCDs) continue to elevate in the western pacific regions, including Vanuatu. Much efforts have been made in reducing the disease burden, however the challenges remains due to certain sociocultural behaviours, globalization, and urbanization which promotes unhealthy lifestyles such as eating lifestyles (unhealthy diet), physical inactivity, harmful use of alcohol and tobacco use. All these contributing factors tends to give rise to common risks for the intermediate factors such as raised in blood pressure, raised in the level of glucose in the blood, the unhealthy lipid profiles, and obesity.Comparing this disease in low-income countries and high-income countries it seem that the rate of NDC are higher in low-income countries, more specifically the countries in the western pacific regions. Even that there are few South East Asian countries such Vietnam, Malaysia, Philippines, and Cambodia which were also regarded as having high mortality rates of NCD (1). According to the profile in 2008 it was estimated that it's the western pacific region that has more of the effect, showing more than a quarter of the 36 million deaths were due to NCD alone.Furthermore it continue to states that the trend will continue to increase by 15% between 2010 and 2020, meaning an estimation (from baseline) from an elevation of up to 44 million deaths will be cause by NCD alone (1). And if we divide the figures up it will then show that the highest proportion will be from the Western Pacific regions, of 12.3 million of deaths, while South-East Asian regions on the other hand is estimated to reach 10.4 million. This is also supported by a report on economic-cost of NCD in the Pacific Island countries which states that NCD is already a challenge in the Pacific, leading to account for 70% or more of the deaths. And the most common cause is of cardiovascular disease, which accounts for between 29% and 38% of death from all other causes (2). In Vanuatu NCD is in the top 10 disease agenda due to fast escalating trend, and similarly are Cardiovascular diseases, including diabetes and hypertension. According to the reported it was estimated that 18% of deaths were due to circulatory heart diseases (7).Another study been conducted in 2008 showed a record of 0.5% and 0.3% deaths were respectively caused by NCD in male and female. The current daily tobacco smoking as a form of behavioural risk factor constitute of 12.3%, where 21.3% in male and 3.1% in female. Additionally from the study record it showed that males are more risks than female in having high blood pressure above normal. This is supported by showing 44.5% of males in the study have raised blood pressure, while female on contrary have 39.1% raised blood pressure. Other contributing factor in the metabolic risks factors are overweight and obesity. From the study it showed that 21% of both male and female are overweight, while 34.2% is of obesity (3).From the findings we have to know that there are unprecedented changes in our environment – cultural, economic, physical, political and social – pose new risks and threats to health. And from most reports and future focus it is predicted that NCD will continue to elevate globally, whether it is urbanization and the built environment, severe air pollution, climate change, unregulated marketing of tobacco and other harmful food products, or easy access to nutrient-poor and calorie dense food (4). In some countries, for instance Vanuatu still accepts more imported and processed food and is predicted to upscale further should the climate conditions such as the current El Nino continue to place threats on garden crops. There is additionally a weak monitoring on food regulations on imported food products and where most labelling are in languages. Lack of proper laboratory analysis of the content against the labelling is another contributing factor. Thus it is imperative that leaders in both Government and related Non-Government Organizations (NGOs) find innovative solutions to complex health challenges in ever-changing common practices and environments. Only then will the population be safe and healthy from the disease. On the other hand we have to understand that at each developmental stage of life, human beings exhibit different vulnerabilities and are exposed to different risks, placing them more vulnerable to contracting those diseases.According to WHO report in 2008 on prevention and control of non-communicable diseases (Annex 1-B) (5), in year 2000 the WHO's Member States adopted a global strategy for prevention and control of NCDs during the fifty-third World Health Assembly. The Global Strategy on Diet, Physical Activity and Health was endorsed in 2002. In 2003, the WHO launched the Framework Convention on Tobacco Control, and this treaty came into force in 2005. Even that in 2008 the Member States endorsed the Action Plan for the Global Strategy for the Prevention and Control of non-communicable Diseases at the Sixty-first World Health Assembly. And the Regional Committee for the Western Pacific called for action to combat non-communicable diseases and their related risk factors in specific resolutions. There are also various regional action plans related to NCD prevention and control (e.g. Regional Plan for Integrated Prevention and Control of Cardiovascular Diseases and Diabetes for the Western Pacific Region 1998–2003, Tobacco Free Initiative Regional Action Plans 2000–2004 and 2005–2009, Plan of Action 2006–2010 for the Western Pacific.Declaration on Diabetes, and the Regional Strategy to Reduce Alcohol-related Harm) were developed over the past decade, sharing a focus on policy and planning, surveillance, health promotion and clinical prevention. Furthermore WHO developed a Pacific Framework for the Prevention and Control of Non-communicable Diseases in 2007 to serve as a guide in addressing NCDs among Pacific island countries and areas, and this framework was adopted by the Secretariat of the Pacific Community (SPC). Augmenting these action plans and frameworks is a Region-wide interest and commitment to fostering health systems change, particularly in relation to the prevention and control of NCDs. In November 2007, the WHO-supported meeting on